A Thing is Whatever This is That I Can't Say: Exploring Aporias through Poetic Inquiry - Coogler, Carlson H. (Art/Research International, 2022)
This inquiry exists because of a necklace I made but could not explain. I picked up theory and poetry and set off on a journey to answer why, and what now. How do you articulate the value of something you remain incapable of explaining? In the middle of the journey, I reached the edge of a ravine. This paper is written there, at the lip of the aporia. It is like a letter or a map. It aims to guide you to that uncrossable gap existing between thing and object, thing and us. It invites you to join me—speaking poems about and into that chasm, and hearing strange replies that might be echoes, or new verses—as I make with and despite and because of the mystery. As I inquire into and with the world, gaps and all, to approach things—that which is that I can’t say.